THE ROLE OF ENTREPRENEURSHIP EDUCATION IN UNIVERSITIES TO PURSUE SUSTAINABLE DEVELOPMENT GOALS - Patricia, Patricia (Universitas Pelita Harapan, 2024)
Flourishing businesses, in contrast to those solely prioritizing profit, have greater potential for innovation, more opportunities, reduced risk, and enhanced resilience in our rapidly changing world. This paper outlines the critical intersection between entrepreneurship education (EE) and the pursuit of UN Sustainable Development Goals (SDGs) within higher education institutions. This paper examines how universities can leverage EE as a stimulant for advancing sustainable development initiatives and fostering a culture of responsible entrepreneurship among students. Drawing on existing literature, the paper explores the multifaceted contributions of EE to the SDGs across various domains, including poverty alleviation, gender equality, environmental sustainability, and economic growth. It highlights the role of EE in equipping students with the knowledge, skills, and mindset necessary to address complex social and environmental challenges through entrepreneurial endeavors. Furthermore, the paper identifies the strategies and best practices for integrating sustainability principles into EE curricula, emphasizing the importance of experiential learning, interdisciplinary collaboration, and community engagement. It also discusses the role of universities as hubs of innovation and research in developing solutions to pressing global issues and fostering entrepreneurial ecosystems that support sustainable development initiatives. Overall, the paper underscores the transformative potential of entrepreneurship education in universities to drive meaningful progress towards the achievement of SDGs. It provides insights and recommendations for educators and practitioners seeking to harness the power of entrepreneurship education to create positive social, environmental, and economic impacts in the pursuit of sustainable development.